The death taboo and suicide prevention at federal universities - Pimentel Rangel Kock, Graciella (Guará Journal, 2023)
The World Health Organization proposed a Mental Health Action Plan with a goal of reducing the global suicide rate by 10%. Brazil signed this plan and implemented a Strategic Action Agenda for Suicide Surveillance and Prevention and Health Promotion for the 2017-2020 period. This proposal included the education sector as a key player and agent of intervention, given that the number of lives lost also affects children, young adolescents, and university students. Therefore, this article analyzes how 15 federal universities in the Southeast and South regions of Brazil work[1] to prevent suicide among members of the academic community and presents suggestions for implementing a Suicide Prevention Program for the Federal University of Espírito Santo (UFES).
Keywords: University; Suicide; Prevention